Effects of inflammation on myopia: evidence and potential mechanisms - Xu, Ran; Zheng, Jing; Liu, Longqian; Zhang, Wenqiu (Frontiers in Immunology, 2023)
As the most common type of refractive error, myopia has become one of the leading causes of visual impairment. With the increasing prevalence of myopia, there is a growing need to better understand the factors involved in its development. Inflammation, one of the most fundamental pathophysiological processes in humans, is a rapid response triggered by harmful stimuli and conditions. Although controlled inflammatory responses are necessary, over-activated inflammation is the common soil for many diseases. The impact of inflammation on myopia has received rising attention in recent years. Elevated inflammation may contribute to myopia progression either directly or indirectly by inducing scleral remodeling, and myopia development may also increase ocular inflammation. This article provides a comprehensive review of the interplay between inflammation and myopia and the potential biological mechanisms, which may present new targets for understanding the pathology of myopia and developing myopia therapies.